1995
DOI: 10.5271/sjweh.6
|View full text |Cite
|
Sign up to set email alerts
|

Single-strand breaks in deoxyribonucleic acid in fire fighters accidentally exposed to o-nitroanisole and other chemicals

Abstract: Objectives The aim of the study was to detect single-strand breaks in deoxyribonucleic acid (DNA) in ~noilonuclear blood cells of fire fighters exposed to o-nitroanisole and other substances released into the environment during an accident in a chemical plant. Methods The level of DNA single-strand brealts in mononuclear blood cells was detected by alkaline elution. The results were compared for 16 fire fighters who worked in a contaminated area for about 8 h and two reference groups (one of fire fighters who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In a recent biomonitoring study of 53 conscripts under education as firefighters, firefighting was associated with increased levels of PAH on the skin, increased urinary excretion of 1‐OHP and increased levels of oxidatively damaged DNA in PBMC [Andersen et al, ]. Municipal firefighters had increased levels of DNA strand breaks in PBMC after a firefighting episode at a chemical plant where they did not wear protective clothing or other safety provisions [Hengstler et al, ]. Another study showed higher levels of DNA strand breaks in PBMC from firefighters as compared to controls, whereas the levels of Fpg‐sensitive sites were similar in the two groups of subjects [Abreu et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent biomonitoring study of 53 conscripts under education as firefighters, firefighting was associated with increased levels of PAH on the skin, increased urinary excretion of 1‐OHP and increased levels of oxidatively damaged DNA in PBMC [Andersen et al, ]. Municipal firefighters had increased levels of DNA strand breaks in PBMC after a firefighting episode at a chemical plant where they did not wear protective clothing or other safety provisions [Hengstler et al, ]. Another study showed higher levels of DNA strand breaks in PBMC from firefighters as compared to controls, whereas the levels of Fpg‐sensitive sites were similar in the two groups of subjects [Abreu et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The frequently analyzed decomposition compound benzene is carcinogenic, but the urinary bladder is clearly not the target tissue. Furthermore, it must be considered that fire fighters might be also exposed to toxic substances due to emergency aid in cases of chemical pollution (Hengstler et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Sudden incidents resulting in contamination of working atmospheres may occur in relation to several work tasks in a number of industries and branches. [4][5][6][7][8][9][10][11][12][13][14] Such incidents of sudden and unintended release of chemicals to the working atmosphere have for instance been reported from fires 15,16 and chemical manufacturing. [17][18][19] Moreover, aircraft cabin air has for several years been of major interest due to alleged in-flight illness and reports of incidents where flight crew members have experienced unexplained health symptoms and sudden air contamination.…”
Section: Environmental Impactmentioning
confidence: 99%